Gender difference in parasympathetic function by HRR1min after graded treadmill exercise in healthy obese young adults - Parimala H Krishnamurthy; Srikanth S (Asian Journal of Medical Sciences, 2023)
Background: Heart rate recovery at 1st min (HRR1min) following exercise, an indicator of parasympathetic function is found to be impaired in obese children, adolescents, and elderly people. In children, adolescents and elderly people impaired that HRR1min was significantly associated with obese females (OF) than in males. This study aims at establishing the gender difference in HRR1min among obese young adults (18–30 years age). Aims and Objectives: This study was conducted to assess parasympathetic function by HRR1min after graded exercise, in apparently healthy obese young adult males and females and to evaluate for gender difference in them. Materials and Methods: Fifty obese young adults (25 males and 25 females with body mass index [BMI] ≥30) and 50 age- and gender-matched controls (25 males and 25 females with BMI ≤24.9) were subjected to graded treadmill exercise. Maximum heart rate reached during exercise and heart rate at 1st min of recovery phase were recorded and HRR1min was calculated as the difference of above. The data were analyzed. Results: The study showed significant decrease in mean HRR1min in obese males compared to OF (mean 18.04±3.6 vs. 30.00±8.55, P<0.001), there is significant delay in HRR1min when OF and males were compared with their gender-matched controls. Conclusion: Parasympathetic function by HRR1min after exercise is significantly decreased in male obese young adults when compared with female obese young adults and are at higher risk of developing metabolic syndrome and cardiovascular disorders.